Elevated soluble Tim-3 correlates with disease activity of systemic lupus erythematosus - Di Zhao; Chunhao Li; Xiao Yang; Wenjiang Yan; Yi Zhang (Taylor & Francis Group, 2021)
T cell immunoglobulin and mucin domain-containing molecule-3(Tim-3) has been found to play important roles in systemic lupus erythematosus (SLE), but whether sTim-3 is involved in the development of SLE remains unknown. In this study, we firstly observed an increased expression of plasma sTim-3 in SLE patients, especially active SLE patients. The plasma sTim-3 levels were positively correlated with anti-dsDNA, SLEDAI score, ESR, and urine albumin. The plasma sTim-3 levels were negatively correlated with C3 and C4. The area under the ROC curve (AUC) values indicated that the plasma sTim-3 level was significantly discriminative of early active SLE from stable SLE and HC with high sensitivity and specificity. The present results suggest that sTim-3 might serve as a potential biomarker for promising the disease activity of SLE.